ACUTE PANCREATITIS AS ADVERSE REACTION Ð¢Ðž PERINDOPRIL THERAPY - Petkovska, Lidija; Josifovik, Fana Licoska; Kavrakova, Julijana Brezovska; Antova, Emilija (Journal of Morphological Sciences; Vol 2 No 1 (2019): JMS, 2019)
Abstract   Many drugs and drug classes have been reported to be associated with acute pancreatitis. Angiotensin-converting enzyme inhibitors are one of the most commonly prescribed classes of medications, as they are used in hypertension, heart failure and proteinuria. Although well tolerated, acute pancreatitis has been reported in a few subjects treated with drugs from this group. We present a rare case of pancreatitis occurring as an adverse reaction to therapeutic doses of perindopril with good outcome. Case report: We report Ð° case of a 63 year-old-woman presented with clinical signs of acute pancreatitis, 2 months after administration of perindopril 4 mg once daily for treatment of hypertension and reduction of proteinuria. The patient has had a 3-year-history of diabetes treated with metformin 2 x 850 mg daily, which is also classified as a possible drug that causes pancreatitis.  Other causes of the disease were ruled out. After cessation of perindopril her clinical status improved and pancreatic enzymes level decreased. Conclusion: Because perindopril has a widespread clinical use, we wish to alert clinicians and urge close monitoring for pancreatitis as well as other adverse effects. Discontinuation of the drug leads to an improvement in the clinical condition. Key words: Angiotensin-converting enzyme inhibitor, Drug-induced pancreatitis, Perindopril